2020
DOI: 10.1002/agj2.20246
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation scheduling technologies reduce water use and maintain turfgrass quality

Abstract: Smart irrigation controllers have demonstrated potential for turfgrass water conservation in humid and temperate environments but have not been comprehensively tested in arid environments. The objective of this study was to determine the accuracy of a wireless capacitance sensor over a wide soil moisture range and to ascertain if smart irrigation controllers resulted in water savings without reducing quality of tall fescue [Schedonorus arundinaceus (Schreb.) Dumort.] and bermudagrass (Cynodon dactylon L.). A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
5
14
1
Order By: Relevance
“…When comparing effects of irrigation treatments on maintenance of visual quality in our study, all treatments supported acceptable quality, with no differences between weather-based or SMS-based approaches. Our observations are consistent with those of Serena et al (2020), who reported acceptable 'Princess 77' bermudagrass summer turf performance when using ET-based, calendarbased, and SMS-based scheduling approaches in a New Mexico study.…”
Section: Irrigation Scheduling Approach Effects On Turfgrass Visual Q...supporting
confidence: 91%
See 1 more Smart Citation
“…When comparing effects of irrigation treatments on maintenance of visual quality in our study, all treatments supported acceptable quality, with no differences between weather-based or SMS-based approaches. Our observations are consistent with those of Serena et al (2020), who reported acceptable 'Princess 77' bermudagrass summer turf performance when using ET-based, calendarbased, and SMS-based scheduling approaches in a New Mexico study.…”
Section: Irrigation Scheduling Approach Effects On Turfgrass Visual Q...supporting
confidence: 91%
“…Differences in K c among studies may be attributed to factors such as fertility, mowing height, or differences in climatic conditions under which studies were conducted. A year‐round K c value of 0.6 was proposed by Meyer and Gibeault (1987) and has been demonstrated to be adequate for maintaining summer bermudagrass quality in multiple studies (Hejl et al., 2016; Serena et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In [ 35 ], soil moisture sensors and evapotranspiration prediction were used to create a better irrigation scheduling, achieving a 39% reduction in water consumption. In [ 36 ] presents a solution capable of reducing 23% of water in irrigation using LoRa nodes that gather information about air temperature and humidity and soil moisture, that were analysed using fog computing.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on turfgrass performance under different irrigation strategies are reported by Serena et al. (2020) and Dyer et al. (2020).…”
mentioning
confidence: 80%
“…Topics also include the effect of fertilization on establishment (Lindsey, Thoms, & Christians, 2020;Øgaard & Aamlid, 2020) and maintenance strategies for disease control (Hempfling, Murphy, & Clarke, 2020;Mattox, Kowalewski, McDonald, Lambrinos, & Pscheidt, 2020). Findings on turfgrass performance under different irrigation strategies are reported by Serena et al (2020) and Dyer et al (2020). We would like to thank Dr. John Stier, University of Tennessee, and Dr. Mike Richardson, Agronomy Journal.…”
mentioning
confidence: 99%